Comparison of the effectiveness of liquid and granule fertilizer mixtures on rubber plants raised by young budding technique - Dharamakeerthi R S; Samarappuli Lalani; Silva S N; Yakandawala A; Yogaratnam N (Journal of the Rubber Research Institute of Sri Lanka, 1997)
Effectiveness of granule fertilizer mixtures was compared with currently used liquid formulations on plants raised by young budding technique. Granule formulations are agronomically effective provided that they are applied in small quantities. Urea based mixtures was found to be comparatively more detrimental than sulfate of ammonia based mixtures when used at concentrations higher than the recommended levels. Currently recommended fertilizer schedule with liquid formulations was the most effective programme for young budding among the treatments tested. Reduced frequency of application increases the deiback percentage significantly. However, it could be applied at two-week intervals instead of weekly intervals equally effectively, thereby reducing the application cost almost by half.
Keywords: Granule fertilizers; Liquid fertilizers; Young budding